Analysis of Key Financial Variables for the Performance of East Nusa Tenggara Regional Owned Water Companies - Anggreini, Reren; Nurafifa; Ramdani, Rahmania; Wu'on, Okto Genrius Basilea; Erwinsyah (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study analyzes the financial performance of PDAMs in East Nusa Tenggara Province from 2019 to 2023 in relation to Return on Equity (ROE), Operating Ratio, and Cash Ratio. Research Methods: After passing traditional assumption tests, multiple linear regression was used to perform quantitative analysis using secondary data from 15 PDAMs (75 observations). Finding/Results: The findings show that while the Operating Ratio has no significant impact on financial performance, ROE and Cash Ratio have a favorable and significant impact. With the highest beta coefficient (0.656), ROE emerges as the most important variable. These results indicate that short-term variations in operational efficiency have a smaller impact on the financial success of PDAMs than the utilization of equity capital and effective liquidity. Conclusion: To improve the financial performance of PDAMs, this report suggests a strategic focus on increasing profitability and strengthening liquidity.